Identification of a person with the help of bite mark analysis - Anoop K. Verma; Sachil Kumar; Sandeep Bhattacharya (Journal of Oral Biology and Craniofacial Research)
Background: Forensic dentistry is an essential part of Forensic science, mainly involves the identification of an assailant by comparing a record of their dentition (set of teeth) with a record of a bite mark left on a victim. Other uses in law for dentists include the identification of human remains, medico-legal assessment of trauma to oral tissues, and testimony about dental malpractice. While the practice of human identification is well established, validated and proven to be accurate, the practice of bite mark analysis is less well accepted. The principle of identifying an injury as a bite mark is complex and, depending on severity and anatomical location, highly subjective. Following the identification of an injury as a bite mark, the comparison of the pattern produced to a suspect's dentition is even more contentious and an area of great debate within contemporary odontological practice. Like fingerprints and DNA, bite marks are unique to an individual – such as distance and angles between teeth, missing teeth, fillings and dental work. This type of impression evidence can be left in the skin of a victim and also can be in food, chewing gum and other miscellaneous items such as pens and pencils. The advent of DNA analysis and its recovery from bite marks has offered an objective method of bite mark analysis.